Efektivitas Media Pembelajaran Lectora Inspire dan Macromath Terhadap Hasil Belajar Matematika - Hafizh Dinar Widianto Putra; Haryono Haryono; Deni Setiawan (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
Lectora Inspire is one of the medias that can assist and overcome the difficulties associated with learning mathematics by connecting the information and fostering knowledge through the active participation of students during the learning process. The purpose of this study is to determine the efficacy of Lectora Inspire media on mathematics learning outcomes. The study employs a quasi-experimental design with a non-equivalent pre-posttest control group design. The study enrolled 58 students using test sheets, documentation, observation, and interviews. The independent sample T-test and the N-gain test are used for data analysis. The results indicated that students in the experimental class who utilized Lectora Inspire media learned mathematics more effectively than students in the control class, with an average increase of 0.57 in the medium category, compared to 0.38 in the control class. The study's findings indicate a significant effect of Lectora Inspire media uses on mathematics learning outcomes. The use of Lectora Inspire media will help students gain a better understanding of mathematics and can accommodate students with a variety of learning methods. According to the findings of this study, teachers should be able to increase the interactive learning process, which will result in more effective implementation of mathematical learning.